2021
DOI: 10.1177/0022034521997112
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and Persistent Salivary Gland Ectasia and Oral Disease After COVID-19

Abstract: The clinical picture of coronavirus disease 2019 (COVID-19) in various target organs has been extensively studied and described. However, relatively little is known about the characteristics of oral cavity involvement. This is surprising, considering that oral mucosal and salivary gland cells are known targets for the direct replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and that the presence of the virus in saliva is a source of transmission of the infection. The aim of our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(152 citation statements)
references
References 38 publications
5
136
1
10
Order By: Relevance
“…Three studies excluded patients who were unable or unwilling to receive a magnetic resonance imaging scan. 27 , 35 , 37 Fourteen studies 8 , 14 , 16 , 19 , 23 , 25 , 27 , 29 , 32 , 35 , 37 , 38 , 44 , 45 did not report reasons for nonparticipation and/or the corresponding number of individuals excluded (eTable 4 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies excluded patients who were unable or unwilling to receive a magnetic resonance imaging scan. 27 , 35 , 37 Fourteen studies 8 , 14 , 16 , 19 , 23 , 25 , 27 , 29 , 32 , 35 , 37 , 38 , 44 , 45 did not report reasons for nonparticipation and/or the corresponding number of individuals excluded (eTable 4 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 9751 total participants, 5266 (54.0%) were male; 30 studies 9 , 10 , 11 , 12 , 13 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 51 , 52 reported mean or median ages younger than 60 years, and 14 studies 9 , 11 , 12 , 13 , 24 , 26 , 27 , 33 , 34 , 35 , 36 , 45 , 46 , 52 reported mean or median ages of 50 years or younger ( Table 1 ). Twenty-four studies 9 , 11 , 12 , 13 , 15 , 19 , 20 , 22 , 23 , 24 , 26 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations